Mapping of Agricultural Land Potency Index in Aceh Besar District Using Geographic Information System - Muhammad Ikbal; Muttaqin Muttaqin (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2018)
Land is an area on the surface of the earth that can produce natural resources for the development of agricultural enterprises. The original income of the district in Aceh Besar comes partly from the agricultural sector, the Land Potential Index has significant significance in its utilization. Land use should be in accordance with the potential land owned on each land. This research uses five parameters in determining Index of Land Potency (IPL) that is slope of slope, rock type (lithology), soil type, rainfall and flood disaster. This research uses blinded and overlapping methods. The result of this research is map of land potential index of Aceh Besar Regency. The map produces five potential classes of land consisting of very low grade, low grade, middle class, high class, and very high class. From the research result, it is found that the area with very low land potential is 4.31%, the area with low land potential is 52.90%, the area with the medium potential is 22.66%, the area with high land potential is 6 , 97% and area with very high land potential that is equal to 13,17%. Sub-districts with the highest widest potential land index in Aceh Besar District are located in Seulimeum, Indrapuri, Kuta Baro and Montasik sub-districts with 4,299.68 ha, 3,938.37 ha, 3,146,23 ha and 3,070,03 ha respectively.Keywords: land potential, geographic Information system, overlapping